Standardised handover process with checklist improves quality and safety of care in the postanaesthesia care unit: the Postanaesthesia Team Handover trial. (December 2021) - Jaulin, François; Lopes, Thomas; Martin, Frederic
Abstract: Background: Miscommunication is a leading cause of preventable incidents in healthcare. A number of checklists have been created in an attempt to improve patient outcomes with only a small impact. However, the 2009 WHO Surgical Safety Checklist demonstrated benefits in terms of reduced morbidity and mortality. Our aim was to determine whether use of a Postanaesthesia Team Handover (PATH) checklist would reduce hypoxaemic events in the postanaesthesia care unit (PACU). Methods: This single-centre, prospective, pre-/post-implementation study was conducted between February 2019 and July 2020 in the PACU of Versailles Private Hospital, Paris, France. Pre-PATH implementation data were collected for 294 consecutive adult patients (≥18 yr old) admitted to the PACU and post-PATH implementation data were collected for 293 consecutive patients. The primary outcome was the rate of hypoxaemic events post-surgery during PACU stay. Results: The rates of hypoxaemic events were 4.1% (11/267 [95% confidence interval CI: 2.3–7.2%]) before the PATH checklist was introduced and 0.8% (2/266 [95% CI: 0.2–2.7%]) after. Patients in the PATH group were 5.6 times (odds ratio [OR] [95% CI: 1.3–33.6], P =0.041) less likely to have a hypoxaemic event than those in the control group. The handover process in the PATH checklist group also had significantly less interruptions (38.6% control vs 20.7% PATH; OR=2.5 [95% CI: 1.7–3.7]; P <0.0001). Conclusions: Implementation of the PATH checklist in adult patients post-surgery was associated with a reduction in the rate of hypoxaemic events in the PACU. These findings support standardisation of the handover process with checklists following anaesthesia and surgery. Clinical trial registration: NCT03972423 .